2015
DOI: 10.4103/0975-9476.146542
|View full text |Cite
|
Sign up to set email alerts
|

Antidiarrheal activity of ethanolic extract of Manihot esculenta Crantz leaves in Wistar rats

Abstract: Background:Use of Manihot esculenta Crantz (MEC) plant has been mentioned in literature of Food and Agriculture Organization of United Nations, Central Tuber Crops Research Institute and many others. It is also known commonly as tapioca, continues to be a crop of food security for the millions of people, especially in the developing countries of the globe including India. Medicinal uses of this plant including diarrhea have been mentioned in literature, but scientific evidence is lacking.Objective:The objectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 21 publications
0
24
0
Order By: Relevance
“…Moreover, many international organizations including WHO have encouraged studies pertaining to the treatment and prevention of diarrheal diseases using traditional medical practices [ 7 – 9 ]. At present, around 25% of drugs are isolated from plants and there are numerous evidences available about the use of medicinal plants including their pharmacological and biochemical properties [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, many international organizations including WHO have encouraged studies pertaining to the treatment and prevention of diarrheal diseases using traditional medical practices [ 7 – 9 ]. At present, around 25% of drugs are isolated from plants and there are numerous evidences available about the use of medicinal plants including their pharmacological and biochemical properties [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Epple et al [23] reported that loperamide exerted anti-secretory effect in the colonic epithelial cells (HT-29/B6) stimulated with forskolin. Loperamide entailed the reduction of intestinal fluid volume accumulation after ig administration of castor oil in rats [24]. Interestingly, Cai et al [25] examined the effect of endomorphin analogues on forskolin-stimulated cAMP production in HEK-293 cells (expressing all ORs) and compared the results to reference ORs agonists.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the inhibition of gut motility can be explained on the basis of presence of alkaloids in the plant, which have been reported to possess anticholinergic property. 17…”
Section: Compounds With Diarrhea-management Actionmentioning
confidence: 99%